2007
DOI: 10.1111/j.1365-313x.2007.03363.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA399 is a long‐distance signal for the regulation of plant phosphate homeostasis

Abstract: SummaryThe presence of microRNA species in plant phloem sap suggests potential signaling roles by long-distance regulation of gene expression. Proof for such a role for a phloem-mobile microRNA is lacking. Here we show that phosphate (Pi) starvation-induced microRNA399 (miR399) is present in the phloem sap of two diverse plant species, rapeseed and pumpkin, and levels are strongly and specifically increased in phloem sap during Pi deprivation. By performing micro-grafting experiments using Arabidopsis, we furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
575
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 671 publications
(615 citation statements)
references
References 52 publications
32
575
0
8
Order By: Relevance
“…The miR399 generated in shoots after the onset of P i starvation serves as a long-distance signal to activate P i transport systems by suppressing PHO2 expression in roots (Lin et al, 2008;Pant et al, 2008). Our results obtained in split-root experiments indicate that CAX1 and CAX3 do not mediate the generation and movement of systemic suppressors from the +P i root half to the 2P i root half.…”
Section: Loss Of Function Of Cax1 and Cax3 Disturbs The Regulation Ofsupporting
confidence: 46%
See 1 more Smart Citation
“…The miR399 generated in shoots after the onset of P i starvation serves as a long-distance signal to activate P i transport systems by suppressing PHO2 expression in roots (Lin et al, 2008;Pant et al, 2008). Our results obtained in split-root experiments indicate that CAX1 and CAX3 do not mediate the generation and movement of systemic suppressors from the +P i root half to the 2P i root half.…”
Section: Loss Of Function Of Cax1 and Cax3 Disturbs The Regulation Ofsupporting
confidence: 46%
“…In accordance with the inverse correlation between miR399 and PHO2 mRNA levels, transgenic plants overexpressing miR399 phenocopied the pho2 mutant and PHO2 T-DNA knockout lines Chiou et al, 2006). Reciprocal micrografting experiments further demonstrated that a pho2 root genotype is sufficient and necessary for P i accumulation in the shoot, whereas the shoot-to-root movement of mature miR399 is responsible for the degradation of PHO2 mRNA in roots (Bari et al, 2006;Lin et al, 2008;Pant et al, 2008). Moreover, upregulation of miR399 by P i deprivation is mediated by the PHOSPHATE STARVATION RESPONSE1 (PHR1) transcription factor, a key positive regulator of multiple P i starvation-induced (PSi) genes (Rubio et al, 2001;Bari et al, 2006).…”
mentioning
confidence: 64%
“…Moreover, transcription factors such as PHR1 (OsPHR1, OsPHR2, PvPHR1, ZmPHR1, TaPHR1), PTF1 (OsPTF1, ZmPTF1), MYB2P-1 (OsMYB2P1), MYB62, WRKY (WRKY75, WRKY6), bHLH32 and ZAT6 are involved in the signalling network to regulate plant adaptation to P stress (Yi et al, 2005;Devaiah et al, 2007a, b;Chen et al, 2007;Valdes-Lopez et al, 2008;Zhou et al, 2008;Devaiah et al, 2009;Chen et al, 2009;Li et al, 2011;Dai et al, 2012;Wang et al, 2013). The posttranscriptional regulation as well as long-distance signal is carried out by microRNAs, for instance miR399 maintain P homeostasis by regulating P transporter PHO2 (Bari et al, 2006;Aung et al, 2006;Lin et al, 2008;Pant et al, 2008). Although the molecular components of P stress signalling in plants has been identified, the overall pathway is still poorly understood and requires further investigation.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A miRNA, miR399, whose precursor was expressed in the shoot, might move from shoot to root via phloem and represses the expression of its target gene. 1 In maize, precursor transcripts of miR390, which is a regulatory factor for the determination of the abaxial side in leaf polarity, Keywords: Arabidopsis thaliana, cell-tocell movement, daxial-abaxial polarity, leaf primordia, MIR165A, miR165, primiR165a…”
mentioning
confidence: 99%
“…Requirement of MIR165A primary transcript sequence for its activity pattern in Arabidopsis leaf primordia Kiyoshi Tatematsu 1, * , Koichi Toyokura 2 , and Kiyotaka Okada 3,4 1 National Institute for Basic Biology; Okazaki, Japan; 2 Graduate School of Science; Kobe University; Kobe, Japan; 3 Department of Agriculture; Ryukoku University; Otsu, Japan; 4 National Institute of Natural Science; Tokyo, Japan m iRNAs might move cell to cell and act as mobile signals in plant development, while the regulatory mechanisms of miRNA cell-to-cell movement are still unclear. Recently, in Arabidopsis leaf primordia, we revealed that miR165 from the MIR165A gene, which is expressed in the abaxial epidermal cells of leaf primordia, acts non-cell-autonomously in inner cells on the abaxial side.…”
mentioning
confidence: 99%